Synthesis, characterization and bio-activity of S-2-picolyldithiocarbazate (S2PDTC), some of its Schiff bases and their Ni(II) complexes and X-ray structure of S-2-picolyl-β-N-(2-acetylpyrrole)dithiocarbazate - Crouse, Karen Anne; Chew, Kar Beng; Tarafder, Md. Tofazzal Hossain; Kasbollah, Azahari; Ali, Abdul Manaf; Mohd Yamin, Bohari; Fun, Hoong Kun (Elsevier, 2004)
A new dithiocarbazate ligand, S-2-picolyldithiocarbazate (S2PDTC) was synthesized using 2-picolylchloride hydrochloride. Tridentate Schiff bases were prepared by condensation of S-2-picolyldithiocarbazate (S2PDTC) with pyridine-2-carboxaldehyde (NNS′), 2-acetylpyrrole (NNS″) and 2-acetylthiophene (NSS), while a bidentate Schiff base (NS) was prepared by condensing the S2PDTC with 2-acetylfuran. Complexes of S2PDTC and its Schiff bases with Ni(II) salts were synthesized and characterized by elemental analyses and various physico-chemical techniques. A square-planar structure has been proposed for the diamagnetic [Ni(S2PDTC)2] and [Ni(NNS″) · Cl] complexes while [Ni(NS) · Cl] complex was dimeric. Complexes of [Ni(NNS′)2] and [Ni(NSS)2] were paramagnetic with octahedral stereochemistry. S2PDTC showed activity against bacteria and fungi (inhibitory zones above 15 mm). The NS and NSS Schiff bases showed activity toward a number of the bacteria assayed, while the NS and NSS Schiff bases, and the [Ni(NNS″) · Cl] and [Ni(NS) · Cl] complexes were found to be active only against C. lypolytica (2075). S2PDTC proved moderately active against HT-29 and weakly active toward CEM-SS with CD50 values of 9.5 and 24.0 μg cm−3, respectively, while among its Schiff bases reported herein, only the NNS′ Schiff base showed strong activity toward CEM-SS (Human cell T-lymphoblastic leukemia) and HT-29 (Human colon adenocarcinoma cells) with CD50 values of 2.3 μg cm−3. All of the Ni(II) complexes were inactive against CEM-SS cancer cells.